2007
DOI: 10.1007/s00299-007-0481-x
|View full text |Cite
|
Sign up to set email alerts
|

Importance of co-cultivation medium pH for successful Agrobacterium-mediated transformation of Lilium × formolongi

Abstract: An efficient system for Agrobacterium-mediated transformation of Lilium x formolongi was established by preventing the drastic drop of pH in the co-cultivation medium with MES. Meristematic nodular calli were inoculated with an overnight culture of A. tumefaciens strain EHA101 containing the plasmid pIG121-Hm which harbored intron-containing beta-glucuronidase (GUS), hygromycin phosphotransferase (HPT), and neomycin phosphotransfease II (NPTII) genes. After three days of co-cultivation on 2 g/l gellan gum-soli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 22 publications
2
26
1
5
Order By: Relevance
“…'Snow Queen' as the long-term reference in our lab (Benedito et al 2005). To date, there have been a few reports aimed to increase transformation efficiency by optimizing the culture conditions in co-cultivation (Azadi et al 2010;Hoshi et al 2005;Ogaki et al 2008). Ogaki et al (2008) found that transient GUS expression and hygromycin-resistant transgenic calli were obtained only when 2-(N-morpholino)ethanesulfonic acid (MES) was added to co-cultivation medium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…'Snow Queen' as the long-term reference in our lab (Benedito et al 2005). To date, there have been a few reports aimed to increase transformation efficiency by optimizing the culture conditions in co-cultivation (Azadi et al 2010;Hoshi et al 2005;Ogaki et al 2008). Ogaki et al (2008) found that transient GUS expression and hygromycin-resistant transgenic calli were obtained only when 2-(N-morpholino)ethanesulfonic acid (MES) was added to co-cultivation medium.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there have been a few reports aimed to increase transformation efficiency by optimizing the culture conditions in co-cultivation (Azadi et al 2010;Hoshi et al 2005;Ogaki et al 2008). Ogaki et al (2008) found that transient GUS expression and hygromycin-resistant transgenic calli were obtained only when 2-(N-morpholino)ethanesulfonic acid (MES) was added to co-cultivation medium. However, we applied co-cultivation medium without MES as suggested by Hoshi et al (2004) and used liquid medium instead of a solid one, which produced both transient and stable GUS expression in multiple callus lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meristematic nodular calli was established in Oriental Hybrid cultivar, 'Acapulco', by using the method described previously (Ogaki et al 2008). They were routinely subcultured every month and the calli of 10-14 days after subculture were used for inoculation with Agrobacterium.…”
Section: Plant Materials and Bacterial Strainmentioning
confidence: 99%
“…Structure of the T-DNA region of pCAMBIA3301:AtSIZ vector provided by Genomine INC (Pohang, Korea) (NPTII (neomycin phosphotransferase); NOS: nopaline synthase promoter; TNOS: 3' signal of nopaline synthase; 35S: Cauliflower Mosaic Virus (CaMV) 35S promoter 수행되어왔다 (Mercuri et al 2003;Nam and Kim 2004;Hoshi et al 2004;Ogaki et al 2008;Azadi et al 2010;Liu et al 2011;Wang et al 2012). 한편 유전자총을 이용한 형질전환 나리식물체 개발에 관한 연구에서는 1998년 최초로 Watad et al (1998) (Hoshino et al 2008;Kim et al 2007;Lin et al 2000), 히야신스 (Popowich et al 2007), 심비디움 (Roh et al 2011 and2013), 팔레놉시스 (Roh et al 2014)나 튤립 (Wilmink et al 1992) 등과 비교하면 형질전환연 구가 비교적 많이 수행되었음을 알 수 있다.…”
unclassified